Photograph of a soldier and two girls with a machine gun and a descriptive note - United States. Army. Signal Corps (photographer):::Creator::::::::::::
This item contains a photograph of a soldier explaining the operation of a machine gun to two 12-year-old YWCA girls, and a typewritten note that describes the photograph.